Facile access to benzofuran derivatives through radical reactions with heteroatom-centered super-electron-donors - Jiang, Shichun (2024)
The development of suitable electron donors is critical to single-electron-transfer (SET) processes. The use of heteroatom-centered anions as super-electron-donors (SEDs) for direct SET reactions has rarely been studied. Here we show that heteroatom anions can be applied as SEDs to initiate radical reactions for facile synthesis of 3-substituted benzofurans. Phosphines, thiols and anilines bearing different substitution patterns work well in this inter-molecular radical coupling reaction and the 3-functionalized benzofuran products bearing heteroatomic functionalities are given in moderate to excellent yields. The reaction mechanism is elucidated via control experiments and computational methods. The afforded products show promising applications in both organic synthesis and pesticide development.